The Evolution of Administrative Systems in Kuwait, Saudi Arabia, and Qatar: The Challenge of Implementing Market Based Reforms. (14th October 2016) - Biygautane, Mhamed; Gerber, Paula; Hodge, Graeme
Abstract: The dramatic plunge in oil prices since the second half of 2014 poses serious challenges for the oil dependent states of Kuwait, Saudi Arabia, and Qatar, and revives their interest in accelerating the implementation of market‐based reforms such as outsourcing, privatization, and public–private partnerships. This article challenges the assumption that these reforms offer a panacea for administrative change, and argues that while they might appear to be a solution to the growing fiscal constraints in the three Gulf states, considerable administrative, cultural, economic, and political barriers hinder their effective implementation. The conclusion reached is that western labels of market‐based reforms offer limited options for the three states in the absence of strong political will to make fundamental reforms that could alter the state–society relations. It is suggested that further theorization of administrative change is required in cultural contexts, such as the Gulf region, where administration and society are intertwined, and where trying to minimize the role and size of the state, poses a direct threat to the political legitimacy of the ruling elites.